(3GdSjQI GdfHhjIs - (3eMeO Hf CMeO Hf GdeSfGhj Hf eMeO Hf CHj HcQ, CHh YHO Gddg GdOdGFj,J (B1136 (3g` s
(3ChdgG (B:s
(3hHYO , aEfi Chdi eG UQa dg GdYfGf GdMOjK Yf SjQI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
,(3gPG HMeO Gddg JeGe eGbUO LeYg , hQLi ai GdOfjG hGdBNQI faYg , adg GdMeO Ydi eG Yde ?, hUdi Gddg hSde Ydi ef HPcQg GdLejd jHOC hjNJe s
(3hGdXGgQ ef GSe GdcJGH ai ebOeJg (B: (3hNdGUI GdMbGFb ef SjQI SjO GdNdGFbs
(3heG jSJJHY Pdc ef GdfcJ hGdObGFbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B259s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B242 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs